THU0290 Effects of biologic dmards on physical function in patients with active psoriatic arthritis: results of network meta-analyses. (12th June 2018) - Ruyssen-Witrand, A.; Sapin, C.; Hartz, S.; Liu Leage, S.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory rheumatic disease associated with psoriasis and characterised by pain, stiffness, swelling of joints, joints ankylosing and low patient quality of life. 1 The economic burden of PsA is substantial 2, and biologic treatments for PsA are increasingly scrutinised in health technology assessments. The most commonly used economic model framework for assessing biologics in PsA is the York Assessment Group model developed as part of a NICE appraisal (the "York model"). 3 In this model improvement in Health Assessment Questionnaire- Disability Index (HAQ-DI) reflects physical function, and is linked to initial treatment response measured by joint improvement assessed by PsARC. Objectives: To assess the effectiveness of biologic DMARDs on HAQ-DI among active biologic-naïve PsA patients through Bayesian network meta-analyses (NMAs) and to understand the relationship to PsARC response. Methods: Data for the NMA was identified through a systematic literature review of published and grey literature (1990-May 2017) in EMBASE/MEDLINE. Bayesian NMAs were conducted in line with NICE guidelines 4 to assess the mean HAQ-DI scores change from baseline for ixekizumab, adalimumab, ustekinumab, etanercept, golimumab, infliximab, apremilast, secukinumab, certolizumab pegol, and placebo in the biologic-naïve overall population as well as in PsARC responders and non-responders. Results were expressed as absolute mean change from baseline and associated standard deviations, and 95% credibility intervals. Results: Overall, 42 publications reporting 19 randomised clinical trials were included for the NMAs, most of these evaluated outcomes at 12 and 24 weeks. Mean changes in HAQ-DI score (overall and by PsARC response) from baseline are shown in figure 1. Among PsARC responders, the greatest mean changes were observed for infliximab, etanercept, ixekizumab, and secukinumab. Among PsARC non-responders, those values were greatest for infliximab, etanercept, ixekizumab Q2W, secukinumab, and adalimumab. The relatively wide 95% credibility intervals reflect the scarcity of available evidence. Conclusions: The results of the NMAs suggest that among the biologic DMARDs infliximab, etanercept, ixekizumab Q2W, secukinumab 150 mg, and certolizumab had the highest HAQ-DI improvements in biologic-naïve patients with active PsA. Changes in HAQ-DI were strongly associated with PsARC response for each treatment. References: [1] Lee S, et al. P T. Dec 2010;35(12):680–689. [2] Kawalec P, et al. Expert Rev Pharmacoecon Outcomes Res2015Feb;15(1):125–132. [3] 3. Woolacott N, et al. Health Technol Assess 2006 Sep;10(31):iii-iv, xiii-xvi, 1–239. [4] Dias SWN, et al. Nice DSU technical support document 2: A generalised linear modelling framework for pairwise and network meta-analysis of randomised controlled trials2011. Disclosure of Interest: A. Ruyssen-Witrand: None declared, C. Sapin Employee of: Eli Lilly and Company, S. Hartz Employee of: Eli Lilly and Company, S. Liu Leage Employee of: Eli Lilly and Company